Palliative care in metastatic head and neck cancer. Issue 9 (21st May 2021) - Civantos, Alyssa M.; Prasad, Aman; Carey, Ryan M.; Bur, Andrés M.; Mady, Leila J.; Brody, Robert M.; Rajasekaran, Karthik; Cannady, Steven B.; Hartner, Lee; Ibrahim, Said A.; Newman, Jason G.; Brant, Jason A.
Abstract: Background: Due to inherent impact on quality of life, metastatic head and neck cancer patients are well‐suited to benefit from palliative care (PC). Our objective was to examine factors that shape PC utilization and implications for overall survival in stage IVc head and neck cancer patients. Methods: A retrospective study of patients with stage IVc head and neck cancer in the National Cancer Database from 2004 and 2015 was conducted. Results: 7794 cases met inclusion criteria, of which 19.3% received PC. PC use was associated with more recent years of diagnosis, Northeast facility geography, and non‐private insurances ( p < 0.05). Compared to no PC, "interventional" PC, defined as palliative surgery, radiation, and/or chemotherapy, and "pain management only" PC were associated with lower overall survival ( p < 0.05). Conclusions: PC use increased over time and was associated with demographic and clinical factors. There remains opportunity for improvement in optimal implementation of palliative care.